Characterization of Endophytic Fungi in Robusta Coffee (Coffea canephora L.) Beans Through 18S rRNA Gene Sequencing and Evaluation of Antioxidant Activity and Chlorogenic Acid Content - Rusman; Nur Alim; Nur Riska Rahma (Postgraduate, University of Mataram, 2023)
Utilizing endophytic fungi to discover metabolites by characterizing the fungi produced from robusta coffee beans can be highly beneficial without causing harm to the plants. Additionally, this approach aids in identifying raw materials for medical drug development, specifically compounds like chlorogenic acid, which hold promise as potential treatments for diabetes mellitus. This study aimed at characterizing the endophytic fungi present in Robusta coffee (Coffea canephora L.) beans through 18S rRNA gene sequencing and evaluation of antioxidant activity and chlorogenic acid content found in these endophytic fungi. Green, unripe Robusta coffee beans were harvested from a coffee plantation in Tana Toraja and isolated using Potato Dextrose Agar medium. The isolation process yielded three isolates, designated RF1, RF2, and RF3. Subsequently, the isolates were subjected to testing for endophytic fungi activity, and the isolate that exhibited activity was further characterized using 18S rRNA gene sequencing. Following that, the isolates were fermented using a Potato Dextrose Broth medium, resulting in two phases: filtrate and biomass. The filtrate was then extracted using ethyl acetate as the solvent. The extracted compound was subsequently evaluated for antioxidant activity using ABTS and DPPH methods, and the concentration of chlorogenic acid was measured. From the three isolates of endophytic fungi obtained from green Robusta coffee beans with the codes RF1, RF2, and RF3, all of them exhibited antibacterial activity against Escherichia coli and Staphylococcus aureus. The 18S rRNA gene sequencing analysis revealed that isolate RF1 was identified as Fusarium sp. For the evaluation of antioxidant activity using the ABTS method, an IC50 value of 53.49 Âµg/mL was obtained, while the DPPH method resulted in an IC50 value of 54.03. Furthermore, the measurement of chlorogenic acid content in the extract of endophytic fungi from Robusta coffee beans indicated a concentration of 11.58%. The characterization result of the endophytic fungi isolates from green Robusta coffee beans revealed the presence of Fusarium sp. It exhibited high antioxidant activity and a chlorogenic acid content of 11.58%.